Proceedings of the 2015 Annual Conference on Genetic and Evolutionary Computation 2015
DOI: 10.1145/2739480.2754778
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Crossover Bias in Genetic Programming

Abstract: In tree-based genetic programming (GP) with sub-tree crossover, the parent contributing the root portion of the tree (the root parent) often contributes more to the semantics of the resulting child than the non-root parent. Previous research demonstrated that when the root parent had greater fitness than the non-root parent, the fitness of the child tended to be better than if the reverse were true. Here we explore the significance of that asymmetry by introducing the notion of crossover bias, where we bias th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Previous work has already shown that the percentage of ancestor individuals having descendants in the last generation is low and that only a small fraction of ancestors contribute genetic material to the solutions in the last generation (Donatucci et al 2014;McPhee et al 2015McPhee et al , 2016. We quantify the fraction of contributing ancestors as the ratio between the size of the trace graph (in which vertices represent ancestors that have contributed a part of their genotype to their descendants in the final population) and the size of the genealogy graph.…”
Section: Contribution Ratiomentioning
confidence: 99%
“…Previous work has already shown that the percentage of ancestor individuals having descendants in the last generation is low and that only a small fraction of ancestors contribute genetic material to the solutions in the last generation (Donatucci et al 2014;McPhee et al 2015McPhee et al , 2016. We quantify the fraction of contributing ancestors as the ratio between the size of the trace graph (in which vertices represent ancestors that have contributed a part of their genotype to their descendants in the final population) and the size of the genealogy graph.…”
Section: Contribution Ratiomentioning
confidence: 99%
“…The constrained dimensionally aware GP was designed in [56] to ensure only semantically correct individuals can be generated to improve the interpretability of evolved rules for JSS. The crossover bias for having the more fit parent as the root parent was presented in [57]. These methods tend to achieve the goal by utilising the semantics of GP individuals during the evolutionary process.…”
Section: Related Work On Genetic Operators Of Gpmentioning
confidence: 99%
“…The constrained dimensionally aware GP was designed based on the types of features in [153] to ensure only semantically correct individuals can be generated to improve the interpretability of evolved rules for JSS. The crossover bias for having the more fit parent as the root parent was presented in [151]. These approaches tend to achieve the goal by utilising the semantics of GP individuals during the evolutionary process.…”
Section: Semantic Crossovermentioning
confidence: 99%